New species from the genera Kansua and Anatlanticus (Orhtoptera: Tettigoniidae) in China - Liu, Chunxiang (Zootaxa, 2015)
The genus Kansua Uvarov was only known in East Asian, and is considered to approach Tettigonia Linnaeus or Glyphonotus Redtenbacher. After comparing male and female specimens of Kansua with other genera of the subfamily Tettigoniinae, we find that Kansua is very similar to Anatlanticus Bei-Bienko and Mongolodectes Bei-Bienko in pronotum, legs, and tegmen rather than Tettigonia and Glyphonotus. Description of one new species Kansua diebua Liu sp. n., of two new species of one newly recorded genus Anatlanticus from China, and first description of male of Mongolodectes alashanicus are presented.